Effectiveness and equity research in Hungarian public education: Systematic literature review 1990-2019 - Fehérvári, Anikó (Iskolakultúra, 2021)
The study presents a systematic literature review on the effectiveness and equity of four major educational journals (Educatio, Iskolakultúra, Magyar Pedagógia, Új Pedagógiai Szemle) in the last three decades. In Hungarian educational research, these two topics are markedly connected. According to our systematic collection of literature, almost a third of Hungarian empirical research focused on this issue. The paper is based on an analysis of 45 articles. It deals with three groups' performance: people with disabilities, socially disadvantaged, and Roma students. The results highlight that in the 1990s, research focused more on the inequalities of education and how they work, while in the 2010s, they focused more on what breaks this pattern and the drivers of resilience.